STUDI LITERATUR PROGRAM FUNDRAISING, STRATEGI FUNDRAISING, DAN KUALITAS INFORMASI AKUNTANSI DALAM MENINGKATKAN PERTUMBUHAN ZIS - Rd. Amar Muslih; Mila Badriyah (Gunung Djati Conference Series, 2025)
This study aims to examine the influence of fundraising programs, fundraising strategies, and the quality of accounting information on the growth of zakat, infaq, and sadaqah (ZIS). Using literature review method, this study analyzes previous research findings related to these variables. The results indicate that well-implemented fundraising programs, especially during the Covid-19 pandemic, significantly influenced ZIS growth. Effective fundraising strategies, including digital fundraising and stakeholder engagement, also play a critical role. Additionally, the quality of accounting information, marked by accuracy, relevance, timeliness, and completeness, enhances transparency and accountability, thus fostering trust among stakeholders and increasing ZIS collections. This research contributes to the development of ZIS management practices, especially for zakat institutions in Indonesia.